Role of CXCR5+ CD8+ T cells in human immunodeficiency virus-1 infection - Gao, Leiqiong; Zhou, Jing; Ye, Lilin (Frontiers in Microbiology, 2022)
Human immunodeficiency virus (HIV) infection can be effectively suppressed by life-long administration of combination antiretroviral therapy (cART). However, the viral rebound can occur upon cART cessation due to the long-term presence of HIV reservoirs, posing a considerable barrier to drug-free viral remission. Memory CD4+ T cell subsets, especially T follicular helper (TFH) cells that reside in B-cell follicles within lymphoid tissues, are regarded as the predominant cellular compartment of the HIV reservoir. Substantial evidence indicates that HIV-specific CD8+ T cell-mediated cellular immunity can sustain long-term disease-free and transmission-free HIV control in elite controllers. However, most HIV cure strategies that rely on expanded HIV-specific CD8+ T cells for virus control are likely to fail due to cellular exhaustion and TFH reservoir-specialized anatomical structures that isolate HIV-specific CD8+ T cell entry into B-cell follicles. Loss of stem-like memory properties is a key feature of exhaustion. Recent studies have found that CXC chemokine receptor type 5 (CXCR5)-expressing HIV-specific CD8+ T cells are memory-like CD8+ T cells that can migrate into B-cell follicles to execute inhibition of viral replication. Furthermore, these unique CD8+ T cells can respond to immune checkpoint blockade (ICB) therapy. In this review, we discuss the functions of these CD8+ T cells as well as the translation of findings into viable HIV treatment and cure strategies.